The behavioral strategies of multiple stakeholders in environmental nimby conflicts: An evolutionary game theoretical research - Long, Zhaoyang; Wang, Sisi; Sohail, Muhammad Tayyab (Frontiers in Environmental Science, 2022)
"Chinese-style Nimby" is a thorny issue in China's current public governance. Generally speaking, there is a game relationship between multiple stakeholders in the environmental NIMBY conflicts. Given this, the study constructs the tripartite evolutionary game model of the government, construction enterprises and the surrounding residents, and uses MATLAB to numerically simulate the evolutionary system. The results show: (1) The effect of government negotiations in resolving environmental conflicts is better than environmental compensation, with the increase in the degree of civil resistance, the probability of the government choosing negotiation strategies will increase; (2) Reducing the cost of negotiations in enterprises, or the taxation index when selecting considering public’s demands, or improving additional benefits of the corporate, which can effectively improve the positivity of enterprises to consider people's appeals; (3) The higher the compensation and the extra benefits of people's cooperative participation are, the faster the system will evolute to people’s cooperative participation. Finally, based on the research findings, this paper provides reference and countermeasures for the construction of multiple co-governance mechanisms of environmental NIMBY conflicts.